Efeitos da fototerapia com energia fracionada do laser de baixa intensidade em células-tronco da polpa de dentes decíduos esfoliados humanos - Almeida Junior, Luciano Aparecido De (2019)
Low-level laser irradiation (LLL) therapy may be able to induce proliferation and differentiation into several cellular types, with remarkable effects in the process of tissue repair, inflammation decrease and analgesia. For pulp repair after conservative procedures, pulp stem cells have the potential to differentiate into odontoblasts and to produce dentine, requiring a specific stimulus to trigger this process. The present study aimed to evaluate in vitro whether the LLL delivering fractionated total energy (multiple irradiation) or single irradiation stimulates regeneration-associated events (viability and proliferation) in stem cells from human exfoliated deciduous teeth (SHED). Cells received LLL irradiation (InGaAlP – 660 nm), according to the following experimental groups: GI (single irradiation: 2.5 J/cm², 10 s, 0.10 J), GII (single irradiation: 5.0 J/cm², 20 s, 0.20 J), GIII (single irradiation: 7.5 J/cm², 30 s, 0.30 J), GIV (2 irradiations: 2.5 J/cm², 10 s, 0.20 J), GV (3 irradiations: 2.5 J/cm², 10 s, 0.30 J) and GVI (non-irradiated). Cell viability was assessed by MTT and trypan blue exclusion (TBE) methods, while cell proliferation was evaluated by crystal violet (CV) and sulforhodamine B (SRB) assays after 24, 48 and 72 hours after the first irradiation. By MTT, there was no difference between groups at 24 and 72 hours. At 48 hours, the groups with multiple irradiation (GIV and GV) presented higher cell viability rates. The mean percentages of viable cells for all groups by TBE method were 91.04%, 96.63% and 97.48% at 24, 48 and 72 hours, respectively. By CV, there was no significant difference between groups at 24 and 48 hours; at 72 hours, GII, GIII and GIV presented higher cell proliferation. By SRB, GI and GIV presented lower proliferation rates in all the periods. When the groups presenting the same total energy were compared, GII (0.20 J) presented lower cell viability rates and higher cell proliferation rates in comparison to GIV; GIII (0.30 J) presented similar results to those of GV, with higher cell viability and proliferation. In conclusion, the application of laser delivering fractionated total energy (2 or 3 applications of 2,5 J/cm²) induced higher cell viability at 48 hours, while the 2.5 J/cm² single irradiation decreased cell viability in such period and proliferation over time. The 5.0 and 7.5 J/cm² single doses and the 3 applications of 2.5 J/cm² maintained cell viability and stimulated proliferation of SHED at 72 hours.